PENGALAMAN IBU HAMIL DALAM MENDAPATKAN PELAYANANANTENATAL CARE ( ANC ) DI RB TETA TAHUN 2017 - Fina Fanka (Jurnal Ilmu Kebidanan, 2018)
Education is a lifelong human need. Educators are required to develop knowledge and skills in an effort to improve the quality of education, especially in the teaching and learning process. Educators must use teaching methods that can make students participate actively in the teaching and learning process such as teaching discussion methods. This study aims to determine the relationship of teaching methods of discussion with the results of learning subjects of midwifery concepts in the first semester students in Medan Healthy Midwifery Academy. This research is correlational with cross sectional research design, Purposive Sampling sampling technique is the first semester C class student amounted 58 respondents. Based on the result of statistical test, it is known that the distribution of teaching teaching method applied by lecturers has good response of 47 people (81%). While the distribution of learning result of midwifery concept subjects get the most B value of 32 people (55,2%). And result of product Moment test with level of trust (α) = 5% (0,05), the result of rhitung ¬ = 0,628 bigger than rtabel = 0,254, so hypothesis accepted "There is relation between teaching method of discussion with study result of subject of midwifery concept ", And has a significant relationship with the level of closeness relationships quite meaningful. It is concluded that the method of discussion is a method that serves to motivate and stimulate students to solve the problem. Suggested to lecturers of midwifery subjects to be able to use more discussion methods on each learning element of the theory, so that midwifery students can improve knowledge and information in interaction to solve the problem.